SARS-CoV-2-specific humoral and cellular immune responses to BNT162b2 vaccine in Fibrodysplasia ossificans progressiva patients - Smetanova, Jitka; Milota, Tomas; Rataj, Michal; Hurnakova, Jana; Zelena, Hana; Horvath, Rudolf (Frontiers in Immunology, 2022)
Introduction: Fibrodysplasia ossificans progressiva (FOP) is characterized by progressive heterotopic ossification triggered by various conditions, such as trauma, infection, including COVID-19 infection, and vaccination. Although SARS-CoV-2 vaccinations prevent poor outcomes in the general population, there is limited evidence on safety, immunogenicity, and efficacy of SARS-CoV-2 vaccines for inpatients with FOP. Methods: A case series of two patients with FOP focused on humoral, cellular post-vaccination response, and the incidence of adverse events after administration of the BNT162b2 vaccine (Comirnaty). Results: Injection site reactions, fever, myalgia, and fatigue were the most common adverse events (AE). Neither severe AE (SAE), nor disease flare-ups were observed. No differences between patients with FOP and healthy controls were observed in humoral and cellular responses. Conclusions: The BNT162b2 vaccine induced high humoral and cellular response levels in patients with FOP. Vaccination was not associated with SAE or disease relapse. The AEs spectrum was comparable to that of the general population.